Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = \(\frac{1}{2}+\frac{5}{6}+\frac{11}{12}+......+\frac{109}{110}\)
A = \(1-\frac{1}{2}+1-\frac{1}{6}+1-\frac{1}{12}....+1-\frac{1}{110}\)
A = \(10-\left(\frac{1}{2}+\frac{1}{6}+\frac{1}{12}+....+\frac{1}{110}\right)\)
A = \(10-\left(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+....+\frac{1}{10}-\frac{1}{11}\right)\)
A = \(10-\left(1-\frac{1}{11}\right)\)
A = \(10-\frac{10}{11}\)
A = \(\frac{100}{11}\)
⇒(x−1)^2+4(y+1)^2+(z−3)^2≥0
x^2+4y^2+z^2-2x-6z+8y+15
=x^2+4y^2+z^2-2x-6z+8y+1+1+4+9
=(x^2-2x+1)+(4y^2+8y+4)+(z^2-6z+9)+1
=(x-1)^2+4(y+1)^2+(z-3^)2+1
Ta thấy:(x−1)^2≥0
4(y+1)^2≥0
(z−3)^ 2≥0
{(x−1)^24(y+1)^2(z−3)^2≥0
⇒(x−1)^2+4(y+1)^2+(z−3)^2≥0
⇒(x−1)2+4(y+1)2+(z−3)2+1≥0+1=1>0